General slavic terminology: main trends of study - Ivashchenko, V.L.; Turovska, L.V.; Kazymyrova, I.A.; Yatsenko, N.O. (Термінологічний вісник, 2013)
The paper attempts to analyze main paradigm, aspectual, cross-paradigm, cross-aspectual and cross-disciplinary trends of study of the general Slavic terminology development in the late XX – early XXI centuries. Fundamental papers of Russian, Ukrainian, Belorussian, Polish, Czech, Bulgarian, Slovakian and Slovenian scholars are systematized according to the existing trends in the field of terminology.